Laser ablation of Ga-Sb-Te thin films monitored with quadrupole ion trap time-of-flight mass spectrometry - Mandal, Govinda; Kotrla, Magdaléna; Nazabal, Virginie; Němec, Petr; Havel, Josef (Wiley-Blackwell, 2021)
Laser ablation of Ga-Sb-Te chalcogenide thin films prepared by radiofrequency magnetron co-sputtering was monitored with quadrupole ion trap time-of-flight mass spectrometry (QIT-TOF-MS). The mass spectra of 11 thin films of various compositions (Ga: 0-53.1, Sb: 0-52.0, and Te: 0-100.0 at. %) were recorded. Several series of unary (Ga-x, Sb-y, and Te-z), binary (GaxSby, GaxTez, and SbyTez), and ternary GaxSbyTez clusters were identified in both positive and negative ion modes. Stoichiometry of observed clusters was determined. Up to 18 binary clusters (positively and negatively charged) were detected for thin film with low Sb content of 6.5 at. %. The highest number (4) of ternary clusters was observed for thin film with high Te content of 66.7 at. %. The number of generated clusters and their peaks intensity varied according to the chemical composition of thin films. Altogether, 41 clusters were detected. The laser ablation monitoring shows laser-induced fragmentation of thin film structure. The relation of clusters stoichiometries to the chemical composition of thin films is discussed. The fragmentation can be diminished by covering a surface of thin films with paraffin's, glycerol, or trehalose sugar thin layers. The stoichiometry of generated clusters shows partial structural characterization of thin films.
Laserová ablace tenkých vrstev Ga-Sb-Te monitorovaná pomocí hmotnostní spektrometrie s kvadrupólovou iontovou pastí
Keywords: amorphous chalcogenides; clusters; Ga-Sb-Te; laser ablation; mass spectrometry; thin films; amorfní chalkogenidy; klastry; Ga-Sb-Te; laserová ablace; hmotnostní spektrometrie; tenké vrstvy